Willingness to switch to EV passenger transport services in Vietnam: Insights for sustainable mobility in developing economies - Luu, Duong Thi Thuy; Phan, Quyet Dinh; Nguyen, Uyen Thi; Nguyen, Van Thi; Anh, Ngo Hoang Quynh (International Journal of Management and Sustainability, 2026)
Environmental pollution, energy scarcity, and advancements in electric vehicle (EV) technology are critical global issues. Combining these factors offers a promising solution for sustainable transportation development, particularly for emerging economies like Vietnam, through the implementation of green mobility solutions via EV passenger transport services (EVPTS). This study investigates the motivations behind the willingness to switch from internal combustion engine vehicles to EVPTS. It focuses on factors related to the perceived benefits of EVs and individual pro-environmental characteristics. Data were collected from a survey of 352 individuals in Hanoi, Vietnam, and analyzed using SmartPLS 4.0 software. The findings revealed a significant positive correlation among environmental concerns, environmental personal norms, perceived inconvenience of private vehicles, and the perceived usefulness of EVPTS. Moreover, excluding the factor of environmental concerns, willingness to switch to EVPTS was positively correlated with perceived usefulness of EV (β=0.380), perceived inconvenience (β=0.318), and environmental personal norms (β=0.251). The major contribution of this study is twofold: First, by selectively combining elements of the Technology Acceptance Model (TAM) and the Norm Activation Model (NAM) and adding the concept of "Perceived inconvenience," our study develops a more comprehensive framework for understanding this behavioral shift. Second, this study demonstrates how perceived benefit attributes (encompassing the benefits of EVPTS and the inconvenience of personal transport), as well as individuals’ pro-environmental characteristics, influence their willingness to switch to EVPTS within the context of a developing country. These findings further provide a foundation for suggesting managerial implications to foster the shift to EVPTS in Vietnam.